2006
DOI: 10.1002/prot.21201
|View full text |Cite
|
Sign up to set email alerts
|

Towards in silico lead optimization: Scores from ensembles of protein/ligand conformations reliably correlate with biological activity

Abstract: Accurately ranking protein/ligand interactions and distinguishing subtle differences between homologous compounds in a virtual focused library in silico is essential in a structure-based drug discovery program. In order to establish a predictive model to design novel inhibitors of dihydrofolate reductase (DHFR) from the parasitic protozoa, Cryptosporidium hominis, we docked a series of 30 DHFR inhibitors with measured inhibition constants against the crystal structure of the protein. By including protein flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…13 The chemical space available for a ligand can also be modeled through docking using an ensemble of structures to develop a pharmacophore for a flexible P450 molecule, as has been recently employed for dihydrofolate reductase. 52,53 Computational solvent-mapping studies revealed the importance of local conformational changes to the promiscuity of P450 enzymes. 54 This study rationalizes for the first time the malleability and promiscuity of ligand binding to P450 enzymes by considering the thermodynamic fidelity of the binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…13 The chemical space available for a ligand can also be modeled through docking using an ensemble of structures to develop a pharmacophore for a flexible P450 molecule, as has been recently employed for dihydrofolate reductase. 52,53 Computational solvent-mapping studies revealed the importance of local conformational changes to the promiscuity of P450 enzymes. 54 This study rationalizes for the first time the malleability and promiscuity of ligand binding to P450 enzymes by considering the thermodynamic fidelity of the binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…There is now significant evidence showing that the use of an ensemble of target structures during docking improves enrichment and ligand ranking 1,3,10,3437. There are many approaches to determining the appropriate weight for the individual ensemble member scores.…”
Section: Discussionmentioning
confidence: 99%
“…Both methods failed (for details, see SI) to reproduce the X-ray structure of COX-1 bound AA as the energetically lowest configuration. In a recent study, Anderson and coworkers (40) showed reliable correlations between calculated and experimental biological activity when using a scoring function averaged over an ensemble of docking complexes. Similar to this concept, 50 snapshots were generated from the final section of the MD simulation, and the average binding affinity between ligand and COX-1 was computed using the ChemScore scoring function (41).…”
Section: Preparation Of Conditioned Media and Quantitation Of Vitaminmentioning
confidence: 99%